IMPLEMENTASI TEORI QUANTUM TEACHING DALAMPEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Edimizwar; Warul Walidin; Syabuddin; Salami Mahmud (Jurnal Tarbiyah Almuslim, 2024)
The focus of the research is how is the implementation of quantum teaching theory in learning Islamic Religious Education? This research uses a qualitative approach and a type of library research. The data obtained from the research were analysed by descriptive method. The results showed that the application of quantum teaching theory in learning Islamic religion consists of several stages, namely educators must give examples to their students, make the learning environment comfortable and fun, and make students happy. In Islamic religious education, the advantages of applying quantum teaching theory can be seen from several things, namely integrity (honesty), failure is the beginning of success, speaking with good intentions, living in the present, commitment, responsibility, flexible attitude, and balance. The role of Islamic education teachers in carrying out activities through the application of quantum teaching theory is (1) encouraging students by providing rich learning recitations that are well designed to enhance the development of students' spiritual, intellectual, emotional, and social potential, (2) often giving positive motivation to students by interacting with them, (3) telling the benefits of learning a material, and (4) participating as a person who is happy to help, can lead and assert, and inspire by fostering curiosity and enthusiasm.